2020
DOI: 10.1371/journal.pone.0240918
|View full text |Cite
|
Sign up to set email alerts
|

Transition from pediatric to adult care for adolescents living with HIV in South Africa: A natural experiment and survival analysis

Abstract: Objective To determine rates of retention and viral suppression among adolescents living with perinatally-acquired HIV who remained in pediatric care compared to those who transitioned to adult care. Methods We evaluated a natural experiment involving adolescents living with perinatally-acquired HIV who were attending a government-supported antiretroviral clinic in KwaZulu-Natal, South Africa. Prior to 2011, all adolescents transitioned to adult care at 12 years of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…This is the first transition readiness assessment developed and validated specifically for ALPH in South Africa. Currently, there are no clear guidelines on how to best determine healthcare transition readiness for ALPH in South Africa [30][31][32]. The HARTS is rapid self-administered 15-question questionnaire that could be integrated into busy clinics to determine adolescent readiness to transition or adapted to other settings to assist in healthcare transition for ALPH.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first transition readiness assessment developed and validated specifically for ALPH in South Africa. Currently, there are no clear guidelines on how to best determine healthcare transition readiness for ALPH in South Africa [30][31][32]. The HARTS is rapid self-administered 15-question questionnaire that could be integrated into busy clinics to determine adolescent readiness to transition or adapted to other settings to assist in healthcare transition for ALPH.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a South African study found that youth had higher retention rates if they remained in paediatric care, when compared with a historical cohort that was transitioned to adult care [6]. These disparities highlight the importance of careful planning and follow-up when transitioning youth living with HIV from paediatric to adult care settings.…”
Section: Introductionmentioning
confidence: 99%
“…These cultural differences between clinics may have significant clinical consequences: a study analyzing HIV outcomes in a multicentre USA‐based cohort found that youth living with HIV receiving care in adult medical settings were more likely to discontinue antiretroviral therapy when compared to those receiving care in paediatric settings [5]. Similarly, a South African study found that youth had higher retention rates if they remained in paediatric care, when compared with a historical cohort that was transitioned to adult care [6]. These disparities highlight the importance of careful planning and follow‐up when transitioning youth living with HIV from paediatric to adult care settings.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has the largest antiretroviral therapy (ART) program along with highest burden of adolescents living with HIV (ALHIV) in the world [ 1 ]. Survivors of perinatally acquired HIV are now reaching adolescence and beyond, yet the majority of adolescents are poorly prepared for the transition from pediatric to adult care services [ 2 , 3 ]. An estimated 320,000 adolescents with perinatally acquired HIV will transfer from pediatric-based or adolescent-based clinics to adult services in the next 10 years in South Africa [ 4 ].…”
Section: Introductionmentioning
confidence: 99%